Associations Among Fatty Acids, Desaturase and Elongase, and Insulin Resistance in Children. (2nd January 2018) - Beccarelli, Lori M.; Scherr, Rachel Erin; Newman, John W.; Borkowska, Alison G.; Gray, Ira J.; Linnell, Jessica D.; Keen, Carl L.; Young, Heather M.
ABSTRACT: Objectives : Fatty acid profiles and desaturase (SCD-16, SCD018, D5D, D6D) and elongase (ELOVL6) enzyme activity have been associated with adiposity and metabolic disease. While this has been studied in adults, few studies have included children. The objective of this study was to evaluate these markers in children and identify relationships with markers of metabolic health. It was hypothesized that these lipid markers would be correlated to adiposity and metabolic disease. Methods : This study was a cross-sectional analysis of fourth- and fifth-grade children (n = 86, aged 9–12) participating in a comprehensive nutrition program. Any student enrolled in the program was eligible for inclusion in this study. Fasting plasma was collected and analyzed for total fatty acids, glucose, insulin, and full lipid panels. Insulin resistance was estimated using calculated homeostatic model assessment for insulin resistance (HOMA-IR) values. Results : There were no differences in lipid markers, glucose, insulin, or HOMA-IR among children classified as normal weight, overweight, or obese. SCD-16, D5D, and ELOVL6 activity was significantly correlated to HOMA-IR values (r = 0.39, p = 0.001; r = −0.33, p = 0.006; r = −0.37, p = 0.005, respectively). In regression analysis, body mass index for age percentile, D6D activity, ELOVL6 activity, and systolic blood pressure were the most significant predictors of HOMA-IR values (adjusted r 2 = 0.39, p ≤ 0.001). Conclusions : There was no relationship between these lipid markers and adiposity in this population; however, there were correlations with HOMA-IR. Regardless of adiposity, there may be underlying changes in fatty acid and lipid metabolism associated with the development of metabolic diseases.